2008
DOI: 10.1088/0022-3727/41/21/215402
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization and thermal stability of Sn-doped Ge2Sb2Te5phase change material

Abstract: The influence of Sn doping on the crystallization and thermal stability of Ge2Sb2Te5 phase change material was studied. Thermal analysis shows that the phase change of Sn7.0Ge20.6Sb20.7Te51.7 occurs slightly higher than that of Ge2Sb2Te5 at 154 °C and has a lower melting point at 536 °C. The activation energy for crystallization for this material is also higher. It has a face-centred-cubic crystal structure. A fast crystallization speed of 60 ns is realized upon irradiation by a blue laser beam of 405 nm. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…Secondly, as a general feature of phase change materials, there is a severe volume shrinkage (6.5%–9.6%910) and corresponding increase in mass density upon crystallisation, which applies considerable mechanical stresses in the PCM cells11, and consequently, causes resistance drift and void formation in the device that finally limits the cyclability of the memory cells. In order to address these issues, other elements including nitrogen12, oxygen13, silicon14, tin15, carbon6, and tungsten16 as well as oxides such as SiO 2 17and Ta 2 O 5 18have been incorporated into the Ge 2 Sb 2 Te 5 material, leading to a higher crystallisation temperature with longer retention times and a reduced residual stress with smaller density change during the phase transition1018.…”
mentioning
confidence: 99%
“…Secondly, as a general feature of phase change materials, there is a severe volume shrinkage (6.5%–9.6%910) and corresponding increase in mass density upon crystallisation, which applies considerable mechanical stresses in the PCM cells11, and consequently, causes resistance drift and void formation in the device that finally limits the cyclability of the memory cells. In order to address these issues, other elements including nitrogen12, oxygen13, silicon14, tin15, carbon6, and tungsten16 as well as oxides such as SiO 2 17and Ta 2 O 5 18have been incorporated into the Ge 2 Sb 2 Te 5 material, leading to a higher crystallisation temperature with longer retention times and a reduced residual stress with smaller density change during the phase transition1018.…”
mentioning
confidence: 99%
“…Fig. 3 shows the curves of sheet resistance versus time at various isothermal annealing temperature for [Ge 2 Sb 2 Te 5 (4 nm)/SnSe 2 (10 nm)] 7 and Arrhenius plot of data retention based on different Ge 2 Sb 2 Te 5 /SnSe 2 films showing extrapolated temperature for 10 years data retention. It can be seen that the higher isothermal annealing temperature leads to shorter failure time, which means that the crystalline grain growth in phase change process is faster.…”
Section: Resultsmentioning
confidence: 99%
“…And the pump power of all the curves is 15 mW. Each curve is measured based on different spots on the surface of the same sample of amorphous [Ge 2 Sb 2 Te 5 (4 nm)/SnSe2 (10 nm)] 7 film to ensure that all the measurements were taken under the same condition. The increasing laser-irradiation power is from 20 to 44 mW.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that a relatively weak bonding strength can cause a significant increase of the crystallization speed in phase change materials. [11][12][13] For example, Ge-Te has a bond energy of 397 kJ/mol that is larger than Sn-Te bond (359 kJ/mol). Therefore replacement of Ge-Te by Sn-Te with weak bonding energy will increase the crystallization speed.…”
mentioning
confidence: 99%